Disruption of SOX6 gene using CRISPR/Cas9 technology for gamma‐globin reactivation: An approach towards gene therapy of β‐thalassemia. Issue 11 (16th July 2018) - Shariati, Laleh; Rohani, Fattah; Heidari Hafshejani, Nahid; Kouhpayeh, Shirin; Boshtam, Maryam; Mirian, Mina; Rahimmanesh, Ilnaz; Hejazi, Zahra; Modarres, Mehran; Pieper, Ina Laura; Khanahmad, Hossein
Abstract: Elevation of Hemoglobin F ameliorates symptoms of β‐thalassemia, a common autosomal recessive disorder. The transcription factor SOX6 plays a key role in the γ to β‐globin gene switching. In the current investigation, a mutation was induced using the CRISPR/Cas9 technology in the binding domain region of SOX6 to reactivate γ‐globin expression. Three CRISPR/Cas9 cassettes were provided, whose single‐guide RNAs targeted different regions in the SOX6 gene‐binding domain. After transfection of K562 cells with CRISPR a, b and c, and subsequent erythroid differentiation, the indel percentage of the cells was about 30%, 25%, and 24%, respectively. Relative quantification showed that the γ‐globin mRNA level increased to 1.3‐, 2.1‐, and 1.1‐fold in the cells treated with CRISPR/Cas9 a, b, and c, respectively, compared with untreated cells. Our results show that mutation induction in the binding site of the SOX6 gene leads to γ‐globin reactivation. These findings support the idea that CRISPR interrupts the SOX6 binding site, and, as a result, SOX6 is incapable of binding the γ‐globin promoter. In conclusion, SOX6 disruption could be considered as a therapeutic approach for β‐thalassemia treatment. CRISPR/Cas9 was selected for this purpose as it is the most rapidly evolving technology. Abstract : In the present research, taking advantage of a novel genome editing tool, CRISPR, we have targeted the SOX6 gene as a potential gene therapy target to elevate fetal hemoglobin (HbF) levels in cell lines. This strategy is rather straightforward and can serve as a therapeutic modality for beta thalassemia after sufficient in vivo experiments are conducted. The highlights of our findings are as follows: Using the CRISPR technology, indel in SOX6 gene was induced. Cleavage in SOX6 gene occrured. The gamma globin gene was overexpressed.